2018
DOI: 10.1080/10376178.2018.1507677
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MAGNET hospital designation on nursing culture: an integrative review

Abstract: Twenty-nine key studies were identified and were evaluated utilising two study quality appraisal tools; National Health and Medical Research Council (NH&MRC) levels of evidence and the Polit and Beck critical appraisal tool. Three key categories emerged from the data: (1) nurse practice environment; (2) structure and process models; (3) measurement scales. A key finding was that MAGNET designation appears to enhance organisational culture for nurses and the framework used to introduce MAGNET helps to empower n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
1
17
0
1
Order By: Relevance
“…Magnet institutions strive to create a culture of quality patient care and nursing excellence through the use of EBP (Anderson et al, 2018). However, nurses experience numerous barriers to EBP implementation, including inadequate knowledge and skills as a result of how EBP continues to be taught in academic settings; hospital cultures steeped in long‐standing traditional approaches to care (e.g., that is how we have always done it here); inaccurate perceptions about the time it takes to engage in EBP; lack of leadership support and resources for EBP; and a lack of EBP mentors available to assist point‐of‐care providers (Li, Cao, & Zhu, 2019; Melnyk & Fineout‐Overholt, 2019; Melnyk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Magnet institutions strive to create a culture of quality patient care and nursing excellence through the use of EBP (Anderson et al, 2018). However, nurses experience numerous barriers to EBP implementation, including inadequate knowledge and skills as a result of how EBP continues to be taught in academic settings; hospital cultures steeped in long‐standing traditional approaches to care (e.g., that is how we have always done it here); inaccurate perceptions about the time it takes to engage in EBP; lack of leadership support and resources for EBP; and a lack of EBP mentors available to assist point‐of‐care providers (Li, Cao, & Zhu, 2019; Melnyk & Fineout‐Overholt, 2019; Melnyk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Keperawatan merupakan salah satu bidang ilmu yang mandiri. Keperawatan sebagai sebuah profesi mempunyai peranan penting dalam upaya meningkatkan pelayanan kesehatan serta sebagai inovator dan agen perubahaan (Anderson, V. L., Johnston, A., Massey, D., & Bamford-Wade 2018) Studi pada beberapa Negara di Asia termasuk Iran, Thailand, dan Filipina menunjukkan perawat memiliki otonomi untuk merawat pasien, termasuk dalam pengambilan keputusan dan terapi pasien. Kemandirian ini berdampak positif bagi pasien dan perawat itu sendiri (Labrague, McEnroe-Petitte, and Tsaras 2019).…”
Section: Pendahuluanunclassified
“…In developed countries, they know that nurses have a crucial role in enhancing health service. It can be seen that nurses lead the patient care and are innovators and change agents ( Anderson et al, 2018 ). The study in Asian countries, including Iran, Thailand, and the Philippines, showed nurses have autonomy for treating their patients, including being involved in decision-making and patient therapy.…”
Section: Introductionmentioning
confidence: 99%